Students’ Intention to Take E-Learning Courses During the COVID-19 Pandemic: A Protection Motivation Theory Perspective - Nguyen, Hoai Than; Tang, Chia Wei (International Review of Research in Open and Distributed Learning, 2022)
This study proposes a new model for integrating the protection motivation theory (PMT) with the technology acceptance model (TAM) to explore factors affecting students’ intention to attend e-learning courses during the COVID-19 pandemic. A total of 432 valid responses to an online questionnaire were received from freshmen students studying in universities in Vietnam and Taiwan. Structural equation modeling was used to evaluate the proposed research model and test the hypotheses, and model evaluation reflected a good fit between the data and the proposed research model. Differences between perceived vulnerability, perceived severity, and intention to take e-learning courses across two countries were also established, suggesting that both the TAM and the PMT should be considered for use in studies related to technology adoption in the pandemic context. The factors influencing students’ intentions to take online courses can be quite varied when different educational settings are considered; therefore, a more contextual understanding of students’ e-learning intentions during pandemic times should be carefully examined. Suggestions for governments and policy makers are also proposed.